Developing a Sustainable and Circular Bio-Based Economy in EU: By Partnering Across Sectors, Upscaling and Using New Knowledge Faster, and For the Benefit of Climate, Environment & Biodiversity, and People & Business - Lange, Lene; Connor, Kevin O.; Arason, Sigurjon; Bundgård-Jørgensen, Uffe; Canalis, Antonella; Carrez, Dirk; Gallagher, Joe; Gøtke, Niels; Huyghe, Christian; Jarry, Bruno; Llorente, Pilar; Marinova, Mariya; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
This paper gives an overview of development of the EU-bioeconomy, 2014-2020. The Vision of the new Circular Bio-based Economy, CBE is presented: Unlocking the full potential of all types of sustainably sourced biomass, crop residues, industrial side-streams, and wastes by transforming it into value-added products. The resulting product portfolio consists of a wide spectrum of value-added products, addressing societal and consumer needs. Food and feed, bio-based chemicals, materials, health-promoting products; and bio-based fuels. The pillars of CBE are described, including biotechnology, microbial production, enzyme technology, green chemistry, integrated physical/chemical processing, policies, conducive framework conditions and public private partnerships. Drivers of CBE are analyzed: Biomass supply, biorefineries, value chain clusters, rural development, farmers, foresters and mariners; urgent need for climate change mitigation and adaptation, and stopping biodiversity loss. Improved framework conditions can be drivers but also obstacles if not updated to the era of circularity. Key figures, across the entire BBI-JU project portfolio (2014-2020) are provided, including expansion of biomass feedstocks, terrestrial and aquatic, and an impressive broadening of bio-based product portfolio, including higher-value, health-promoting products for man, animal, plants and soil. Parallel to this, diversification of industrial segments and types of funding instruments developed, reflecting industrial needs and academic research involvement. Impact assessment is highlighted. A number of specific recommendations are given; e.g. including international win/win CBE-collaborations, as e.g. expanding African EU collaboration into CBE. In contrast to fossil resources biological resources are found worldwide. In its outset, circular bio-based economy, can be implemented allover, in a just manner, not the least stimulating rural development.